2008
DOI: 10.1111/j.1099-1123.2008.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Auditor Choice: Evidence from a Small Client Market

Abstract: This paper analyzes the auditor choices for a sample of 2,333 predominantly small and mid-sized Finnish firms. Finland requires virtually all commercial enterprises to have a financial statement audit, but allows the smallest firms to choose from four types of audit firms: first tier international firms, first tier national firms, second tier local auditors and non-certified auditors. We find that among the smallest firms, the choice to hire a certified auditor relates to the level of complexity in the organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
158
3
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(178 citation statements)
references
References 71 publications
14
158
3
3
Order By: Relevance
“…DT, NNs and logistic regression, all agree that the most signifi cant input variable is the variable Total Debt, and Audit Fees is also included in the list of signifi cant variables. This conclusion complies with the fi ndings of DeFond (1992); Firth (2002); Broye and Weill (2008) and Knechel et al (2008). …”
Section: The Models' Development and Interpretationsupporting
confidence: 78%
See 2 more Smart Citations
“…DT, NNs and logistic regression, all agree that the most signifi cant input variable is the variable Total Debt, and Audit Fees is also included in the list of signifi cant variables. This conclusion complies with the fi ndings of DeFond (1992); Firth (2002); Broye and Weill (2008) and Knechel et al (2008). …”
Section: The Models' Development and Interpretationsupporting
confidence: 78%
“…A recent study by Knechel et al (2008) analysed auditor nomination by Finnish fi rms using logistic regression analysis. They found that the need for a higher quality auditor is fi rst driven by complexity, and then, as the fi rm grows, it is supplemented by the use of debt fi nancing and ultimately by the need to raise equity as well as debt fi nancing.…”
Section: Prior Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reasons behind this argument is that in Finland virtually all businesses regardless of size are required to report public financial statements that are subject to full financial statement audit (Knechel, Niemi, & Sundgren, 2008).…”
Section: The Finnish Contextmentioning
confidence: 99%
“…Following previous studies, we include a set of control variables for different aspects of audit complexity, which can have an impact on firm's demand for audit quality. To control for organizational complexity we define the variable SIZE as a natural logarithm of total assets, and the variable GROUP, indicating whether the firm belongs to a corporate group (i.e., the firm is a parent company, a subsidiary or a jointly controlled company) (Knechel et al, 2008). To control for the transactions complexity, we define the variable A_TURN as a ratio of sales to total assets, and the variable EXPORT, indicating whether the firm has foreign sales (Chaney et al, 2004).…”
Section: Control Variablesmentioning
confidence: 99%